2007
DOI: 10.1111/j.1365-2966.2006.11274.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical distributions of galactic   spin parameters from the Sloan Digital Sky Survey

Abstract: Using simple dimensional arguments for both spiral and elliptical galaxies, we present formulae to derive an estimate of the halo spin parameter λ for any real galaxy, in terms of common observational parameters. This allows a rough estimate of λ, which we apply to a large volume‐limited sample of galaxies taken from the Sloan Digital Sky Survey data base. The large numbers involved (11 597) allow the derivation of reliable λ distributions, as signal adds up significantly in spite of the errors in the inferenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(97 citation statements)
references
References 41 publications
14
80
3
Order By: Relevance
“…The spheroids have always lower median values than the disk galaxies (see also Table 5 for the fitting parameters). Observationally, Hernandez et al (2007) also found that the spiral galaxies on average have larger λ-values than the ellipticals of their sample. However, this was not seen in previous studies by Sales et al (2012) and Scannapieco et al (2009), who did not find a correlation between galaxy type and the spin parameter.…”
Section: The Spin Parameter λ Of the Host Halosmentioning
confidence: 81%
See 1 more Smart Citation
“…The spheroids have always lower median values than the disk galaxies (see also Table 5 for the fitting parameters). Observationally, Hernandez et al (2007) also found that the spiral galaxies on average have larger λ-values than the ellipticals of their sample. However, this was not seen in previous studies by Sales et al (2012) and Scannapieco et al (2009), who did not find a correlation between galaxy type and the spin parameter.…”
Section: The Spin Parameter λ Of the Host Halosmentioning
confidence: 81%
“…Hernandez & Cervantes-Sodi (2006) calculated the λ-parameter for two galaxy samples with a total of 337 observed spirals and found that with decreasing bulge-to-disk ratio the spirals have increasing λ-values. In a further study Hernandez et al (2007) investigated a sample of 11,597 spiral and elliptical galaxies from the Sloan Digital Sky Survey (SDSS) and found that ellipticals on average have lower λ-values than spiral galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The only unobservable quantity M halo can be replaced by M baryon /F where F is the baryonic fraction, or, alternatively, M * /F d where F d is the stellar disk mass fraction. Based on this framework Hernandez et al (2007) analyzed the empirical λ distribution of samples taken from the SDSS. Because their sample lacked direct measures of V rot , those authors invoked the Tully-Fisher relation to infer V rot from the disk luminosity.…”
Section: Spin Parameters Derived From the Tully-fisher Relationmentioning
confidence: 99%
“…We also require that the r-band light profile should be better fitted by an exponential profile than a deVaucouleurs profile to be sure we were including mainly disk galaxies. Since Hernandez et al (2007) ignored internal extinction but we have corrected for it using the SED fitting estimate of A R , the b/a requirement in our case is less strict, b/a > 0.35. Such a cut is adopted so that the b/a distribution is close to being flat above 0.35.…”
Section: Spin Parameters Derived From the Tully-fisher Relationmentioning
confidence: 99%
See 1 more Smart Citation